Analysis of stakeholder networks for breastfeeding policies and programs in Ghana - Richmond Aryeetey; Kassandra Harding; Amber Hromi-Fiedler; Rafael Pérez-Escamilla (International Breastfeeding Journal, 2020)
Abstract Background Suboptimal breastfeeding practices are driven by multiple factors. Thus, a multi-sectoral approach is necessary to design and implement appropriate policies and programs that protect, promote, and support breastfeeding. Methods This study used Net-Map, an interactive social network interviewing and mapping technique, to: a) identify key institutional actors involved in breastfeeding policy/programs in Ghana, b) identify and describe links between actors (i.e., command, dissemination, funding, and technical assistance (TA)), and c) document actors influence to initiate or modify breastfeeding policy/programs. Ten experts were purposively selected from relevant institutions and were individually interviewed. Interview data was analysed using social networking mapping software, Gephi (version 0.9.2). Results Forty-six unique actors were identified across six actor categories (government, United Nations agencies, civil society, academia, media, others), with one-third being from government agencies. Dissemination and TA links accounted for two-thirds of the identified links between actors (85/261 links for dissemination; 85/261 for TA). Command links were mainly limited to government agencies, while other link types were observed across all actor groups. Ghana Health Service (GHS) had the greatest in-degree centrality for TA and funding links, primarily from United Nations Children’s Fund (UNICEF) and development partners. The World Health Organization, UNICEF, Ministry of Health, and GHS had the highest weighted average relative influence scores. Conclusions Although diverse actors are involved in breastfeeding policy and programming in Ghana, GHS plays a central role. United Nations and donor agencies are crucial supporters of GHS providing breastfeeding technical and financial assistance in Ghana.